Evolutionary perspectives on human behavior during the coronavirus pandemic: Insights from game theory - Brüne, Martin (Evol Med Public Health, 2020)
The coronavirus pandemic constitutes a global challenge to society and medicine. Here, we review evolutionary insights that are relevant for the understanding of how people respond to the pandemic and what to expect in the aftermath of the crisis. Specifically, we argue that the behavioral immune system (BIS) and sickness behavior (SB) comprise two adaptive responses to impending and actual infection, respectively, and that individuals activating their BIS differ from those showing SB in important ways that may have implications for the prevention and treatment of COVID-19. Moreover, we reframe some of the behavioral health issues associated with the pandemic in a game-theoretical scenario, illustrating the difficulties that arise when public health is treated as a ‘public good’. Lay summary: The coronavirus pandemic constitutes a global challenge to society and medicine. In this article, we employ evolutionary theory to improve our understanding of how people respond to the pandemic. Specifically, we argue that human behavior is guided by ancient mechanisms involving either the avoidance of infection or defense against attacks in times of enhanced vulnerability. Moreover, we reframe some of the behavioral health issues associated with the pandemic in a game-theoretical scenario. This helps understand why most people comply with rules of social distancing, while a minority fails to do so for very different reasons. The evolutionary perspective also allows making some predictions for the course of the pandemic.